National minorities and cross-border cooperation between Denmark and Germany - Kühl, Jorgen (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2004)
This article introduces the case of the German-Danish experience on national minorities and cross-border cooperation in their borderlands. Firstly, the region will be characterized. Then the historical background and the present-day situation of the national Danish and German minorities will be described. In the third section, the German-Danish experience will be characterized and summed up in conclusive statements. Then, the development from minority regulations to cross-border cooperation will be characterised. Finally, the impact and relevance of the Schleswig experience to cross-boundary peace-building measures will be pointed out.
Keywords: Danska; Denmark; Germany; Nemčija; obmejna območja; obmejno sodelovanje; narodne manjšine